Traktat Krzysztofa Kluka „Zwierząt domowych i dzikich, osobliwie krajowych, historii naturalnej początki i gospodarstwo” — oświeceniowy podręcznik zoologii - Jerzy Biniewicz (Stylistyka, 2018)
The author focuses on the history of the Polish scientific educational style. The 18th century science in is an area for empirical, theoretical, and practical knowledge of the natural world. The article discusses a Polish text by Krzysztof Kluk, Zwierząt domowych i dzikich, osobliwie krajowych, historii naturalnej początki i gospodarstwo (The beginnings of natural history and husbandry of farmed and wild animals, of domestic animals in particular) (vol. 1, 1779). The author provides us with a basic outline of zoology in 18th century and proposes a lecture on animals living in Poland. His lecture has two narrative planes: scientific and colloquial. In this article, the author proposes a methodology of text analysis. Careful stylistic analysis of 18th century scientific texts shows that Polish handbooks of zoology and economy have features that characterize modern scientific texts, namely bilingual communication, preference for specialist language, rhetorical figures, use of specific verb forms and distinct narrative structure.